The Role of Mast Cells in Irritable Bowel Syndrome - Kang Nyeong Lee; Oh Young Lee (Gastroenterology Research and Practice)
Irritable bowel syndrome (IBS) is one of the most common functional gastrointestinal disorders, but its treatment is unsatisfactory as its pathophysiology is multifactorial. The putative factors of IBS pathophysiology are visceral hypersensitivity and intestinal dysmotility, also including psychological factors, dysregulated gut-brain axis, intestinal microbiota alterations, impaired intestinal permeability, and mucosal immune alterations. Recently, mucosal immune alterations have received much attention with the role of mast cells in IBS. Mast cells are abundant in the intestines and function as intestinal gatekeepers at the interface between the luminal environment in the intestine and the internal milieu under the intestinal epithelium. As a gatekeeper at the interface, mast cells communicate with the adjacent cells such as epithelial, neuronal, and other immune cells throughout the mediators released when they themselves are activated. Many studies have suggested that mast cells play a role in the pathophysiology of IBS. This review will focus on studies of the role of mast cell in IBS and the limitations of studies and will also consider future directions.